Evaluasi Manajemen Kearsipan pada Dinas Kearsipan dan Perpustakaan Kabupaten Kebumen - Salamah, Lisa Nur; Murtopo, Bahrun Ali (IAINU Kebumen, 2024)
This study aims to evaluate the archival management at the Archives and Library Office of Kebumen Regency with a focus on the implementation of the Dynamic Archival Information System (SIKD). The evaluation was conducted through an analysis of the involved human resources (HR), where it was found that the main obstacle was the lack of staff with IT and Archival backgrounds. The method used was descriptive qualitative through interviews, observations and document studies. The results showed that although the implementation of SIKD was smooth, there is a significant need for competence enhancement and the recruitment of IT and archival experts. Furthermore, it was found that effective archival management not only compliance with regulations. The main recommendations from this study are the necessity of intensive training for existing staff and the recruitment of expert personnel to address HR limitations. With these steps, it is expected that the archival management at the Archives and Library Office of Kebumen Regency can be more efficient and effective, supporting the creation of a transparent and accountable government.